PENENTUAN JUMLAH TENAGA KERJA TEORITIS DI STASIUN PENGEMASAN PT. RUMPUN SARI KEMUNING I KARANGANYAR MENGGUNAKAN METODE STUDI WAKTU - , KARINA RAMADHANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
PT Rumpun Sari Kemuning I is engaged in the industry in the processing of semi-finished dry tea. Tea leaf plucked the garden then processedand shipped to domestic consumers and export. This company is located in the Kemuning village, Karanganyar, Central Java. In this packaging stationâs it still uses manual system that is working with the help of labor so that workers donât yet have a standard time for work. Therefore, measurements the standard timeâs labor and known amount of theoretically labor. Determination the amount of theoretical laborâs Rumpun Sari Kemuning I Company aims to improve the effectiveness and efficiency. Method used is the time study to make observations on the time workers 30 times. After that, the normal time can be determined by first determining the rating factor and then the standard time can be determined by first determining allowance factor. By knowing the cycle time, normal time, and standard time so can be determined the amount of theoretically labor. The amount of labor required for each work operation on packaging stationâs PT Rumpun Sari Kemuning as many one person.